Reason and character : the moral foundations of Aristotelian political philosophy - Pangle, Lorraine Smith (Chicago : The University of Chicago Press, 2020)
"This book is a fresh examination of Aristotle's teaching on the relation between reason and moral virtue in the Nicomachean Ethics, taking as its point of departure the oft-noted, but still perhaps not sufficiently appreciated fact, that this treatise is the first half of a two-volume work on political science. As such, it lays the foundation for Aristotelian political science and, in significant ways, for the field of political science altogether. The proper aim of the political community according to Aristotle is to promote the human good; it is the task of the Nicomachean Ethics to elaborate what this good is. It provides Aristotle's fullest answer to the most radical question about justice, the question of why we should be just or moral at all, in its teaching on the essential relation of virtue to happiness"--
The Task and the Puzzle of Reason in the Nicomachean Ethics (NE 1 and 2) -- Knowledge, Choice, and Responsibility for Character (NE 3.1-5) -- Reason and Purpose in the Moral Virtues (NE 3.6-4.9) -- Justice and the Rule of Reason (NE 5) -- Wisdom and Active Wisdom: The Intellectual Virtues (NE 6) -- Problems of Self-Control (NE 7.1-10) -- Epilogue: The Philosophic Life (NE 10.6-8)
Includes bibliographical references (pages 307-313) and index.
Keywords: Aristotle; Ethics, Ancient